Bleu, blanc, gris… la couleur des mariages - Manuela Salcedo Robledo (L'Espace Politique)
In France, daily lives are defined by new “internal” borders between “native” French, “naturalized” French as well as all others who, although not French, live on the French territory, and constitute “a problem” which affects the private lives of single citizens just as it affects governmental action and political discourse. This article brings to light one of these borders, that brands unions of couples or binational marriages, which are more generally called “mixed marriages”. They illustrate the gap that separates “us” (the French) from “them” (foreign nationals from states outside of the European Union). By analyzing the following interviews of two foreign partners of French women, I show that the actual politics of immigration reverberate throughout the personal lives of binational couples. These people can attest to the virtual impossibility of leading a life together, due to the new administrative constraints that the foreign partner must endure during the process of sorting out or obtaining a “Private and Family Life” document (carte de séjour “Vie privée et familiale). New tactical accounts are juxtaposed to romantic relationships, particularly for heterosexual couples. Forced to justify the selfless character of their marriage, not to mention the sincerity of the love that unites them, they test out the practical, political and moral meaning of the borders that organize the social world.